South Korea's middle-power engagement initiatives : perspectives from Southeast Asia - Teo, Sarah (2014)
South Korea has emerged as an important actor in the evolving Asian and global governance structure. Its influence has grown in various capacities that spans over areas such as trade, investment, aid, tourism and the cultural Korean Wave. Today, most analysts acknowledge South Korea’s status as a middle power—both in terms of its material capabilities as well as its foreign policy behaviour. This paper focuses on Southeast Asian perspectives of South Korea’s rise, specifically views from Indonesia, Malaysia, the Philippines, Singapore and Vietnam. It examines these countries’ views of South Korea’s rise and its efforts in promoting itself as a middle power. The paper concludes that Southeast Asia generally views South Korea as an emerging middle power, and its role in Southeast Asia is largely confined to the economic and cultural sectors. Although South Korea is perceptibly absent from Southeast Asia’s geostrategic calculus, its perceived neutrality (despite being a U.S. ally) is seen to work to its advantage in its pursuit of middle power status.